(untitled) (Economics and region, 2024)
The article examines the key aspects of neutralizing risks and threats to global financial security in the current environment. The authors determine that financial security is a key factor in stable economic development, creation of an attractive investment environment and preservation of socio-economic balance. It is substantiated that a breach of financial security can have serious consequences for the country’s economy, threaten its national security, economic security and security of the information environment. The article analyzes the complex interrelationships of national financial systems in the global context, as well as the threats arising from global economic crises; it focuses on the underestimation of risks in martial law. The authors study in detail the areas of ensuring economic and information security of Ukraine, considering its vulnerability due to the instability of the banking system, external debt and other risks that have arisen in connection with the large-scale invasion of Ukraine by the Russian Federation since 2022. The authors suggest ways to neutralize the above risks and propose an organizational and economic structure for regulating financial security as a component of economic security, including five key levels. In addition, the article identifies the main directions of formation of Ukraine’s anti-crisis strategy in the context of both economic and information security, which will contribute to the country’s security-oriented development in the context of globalization.